High-Sensitivity and Fast-Response Graphene/Crystalline Silicon Schottky Junction-Based Near-IR Photodetectors - Lv, Peng; Zhang, Xiujuan; Zhang, Xiwei; Deng, Wei; Jie, Jiansheng (IEEE electron device letters, 2013)
Schottky junction near-infrared photodetectors were constructed by combing monolayer graphene (MLG) film and bulk silicon. Notably, the device could operate at zero external voltage bias because of the strong photovoltaic behavior of the MLG/Si Schottky junction, giving rise to high responsivity and detectivity of 29 mAW -1 and 3.9×10 11 cmHz 1/2 W -1 , respectively, at room temperature. Time response measurement revealed a high response speed of 100 μs, which allowed the device following a fast varied light with frequency up to 2100 Hz. In addition, the device showed great potential for low light detection with intensity at 10 K.